Coping Stress in Overcoming Problems in Performance - Subakti, Surya Tri; Alfita, Laili (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study aims to identify and analyze effective stress-coping strategies in dealing with work problems through the literature review method. This study reviews previous studies involving several professional subjects who face stressful workplace situations. The findings show that coping strategies can be grouped into two categories: problem-focused coping, proven effective when individuals have control over stressful situations and can take direct action to solve problems, such as problem-solving planning and seeking social support. Emotion-focused coping, which includes accepting responsibility and positive reappraisal, is more appropriate when control over the situation is limited, helping individuals manage emotions and remain productive. The conclusion of this study emphasizes the importance of a multidimensional coping approach tailored to the work context and individual characteristics. Implementing several coping strategies, adequate social support, and organizational understanding of employee coping needs can improve well-being and productivity in the workplace. This study recommends developing a comprehensive and integrative stress-coping program to support employees facing several challenges.